Public assessment for environmental management plan implementation: Comparative study of performance indicators of road and highway construction projects - Nurol Huda, Dahalan; Rahimi, A. Rahman; Siti Hafizan, Hassan; Saffuan, Wan Ahmad (American Society of Civil Engineers (ASCE), 2024)
Road and highway construction projects are often a concern among surrounding communities as these projects possess significant risks to the environment, and their impacts can reach far beyond the project areas. Monitoring the environmental management plan (EMP) implementation of road and highway construction projects is challenging as it requires a high level of human resources. Thus, allowing the public to assess and report any potential misconduct in road and highway construction projects can help monitor EMP performances. This study aims to compare key performance indicators (PIs) for assessing EMP implementation in road and highway construction projects. To achieve the aim, the study objectives are to (1) determine the key PIs for road and highway construction projects, (2) develop underlying components that categorize interrelated PIs, and (3) compare the underlying components between road and highway construction projects. To achieve those objectives, this study first develops a questionnaire survey by conducting a systematic literature review and semistructured interviews with industry professionals. Throughout the process, 39 PIs for assessing EMP performances have been identified. Then, a questionnaire survey was developed using the PIs and distributed to environmental professionals, collecting 111 valid responses. Finally, the data for the study were analyzed using mean score ranking, factor analysis, and agreement analysis among the two project types. This study has identified 18 and 21 key PIs for assessing EMP implementation in road and highway construction projects. The key PIs can be categorized under four underlying components for both types of construction projects: geological, pollution, environmental change, and ecological for roads, and pollution, ecological, public safety, and geological for highways. This study adds to the environmental management literature by comparing potential PIs for road and highway construction projects, potentially helping policymakers and industry practitioners develop public assessments for EMP implementation of road and highway construction projects.